Acculturation of Islam and the Sinamot Tradition: Marriage Dynamics of the Angkola Batak Community 1980-2023 - Padlan Padil Simamora; Nurul Hak; Dinda Difia Madina; Ahmad Rezy Meidina; Mega Puspita; Anwar Zein (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2024)
Islamisation in the Indonesian archipelago has been ongoing for centuries. Islam emerged as an influential force in the history of the archipelago. The entry of Islam into Indonesia, a country diverse in culture, led to culture and religion being closely linked. In the Angkola Batak tradition, ancestors' teachings remained embedded in everyday life until after the arrival of Islam, when acculturation and interrelationships took place between Islamic culture and religion. This study uses a qualitative research method, with a library research approach focusing on the acculturation of Sinamot (dowry) culture in the Batak Angkola community of South Tapanuli. The study findings cover three aspects of the topic. First, the social condition of the Angkola Batak community, which adheres to the dalihan na tolu social structure as a benchmark for communicating, acting, and resolving social problems. Second, the interrelationship between customs and Islam in the Sinamot tradition (one of the series in Angkola Batak marriages) in determining the amount of Sinamot is attended by the nuclear family from both parties to resolve the specified amount. Finally, it was discovered that there were changes in the banquets in the deliberation, such as abandoning forms prohibited in Islamic teachings, such as those involving the consumption of pork and palm wine, and also changes in the Sinamot tradition in the marriages of the Angkola Batak community due to several factors, including changes resulting from the move from traditional to modern times, and the wishes of the Batak Angkola community to familiarise themselves with and keep up with the times. The introduction of Islam provided a systematic and logical variation, allowing society to easily accept it at wedding ceremonies.